Pemberdayaan Masyarakat Melalui Budidaya Tanaman Obat Lokal di Gerai Toga Desa Dadapan - Alif, Trisnani; Wahidah, Fita Fitriatul; Aisyah, Mahindra Dewi Nur; Resmi, Fitroh (TAAWUN, 2024)
Dadapan is a village that has local plants that have potential as Family Medicinal Plants (TOGA). This activity aims to transfer information regarding the cultivation and direct practice of local medicinal plants through presentation, discussions, and implantation. This activity includes 1) preparation; 2) Socialization; 3) Toga Cultivation practices and 4) Mentoring. This activity was carried out on August 20, 2023. The results obtained after the activity were an increase in basic knowledge regarding cultivation techniques practiced for family medicinal plants (TOGA) and the establishment of the TOGA Center.